Motivation and Performance of Cadres to Optimize Resilience of Comorbid Diabetes Mellitus in the Covid-19 Pandemic Era - Nur Muji Astuti; Dwi Priyantini; Merina Widyastuti; Ninik Ambar Sari; Christina Yuliastuti; Ceria Nurhayati (Journal of Health Community Service, 2022)
Older adults and people who have a history of chronic disease (comorbid) are more at risk of contracting COVID-19, one of which is diabetes mellitus (DM). The role of cadres is needed to increase the DM patients’ resilience during the pandemic. Optimizing this resilience can be realized in achieving cadres’ performance where motivation is one factor. This activity is performed by increasing information to comorbid diabetes mellitus patients during the pandemic using coaching level, implementation level, and evaluation level. The motivation and performance were measured using questionnaires with observational analysis method. This activity was carried out on December 20, 2020, and was attended by 23 cadres under the guidance of the Candi Sidoarjo Health Center. From the observations and analysis results, it was found that 100% of cadres have high motivation, and 100% of cadres have good performance towards efforts to optimize the resilience of patients with diabetes mellitus comorbid in the Covid 19 pandemic era. Performance is a function of motivation, competence, and work system. The cadres’ self-motivation makes the urge to behave (performance) that provides benefits to others; this will give the cadres some satisfaction (self-actualization) and help to achieve government programs through posyandu activities. The cadres’ involvement is essential in optimizing the resilience of patients with diabetes mellitus comorbid in the Covid 19 pandemic. The motivation and performance of cadres need to be maintained and even increased to create a physically and mentally healthy society.